PENGARUH TEKNIK RELAKSASI TERHADAP PENURUNAN SKALA NYERI POST OPERASI DI RUMAH SAKIT Dr.OEN SURAKARTA - Diyono Diyono; Sriyani Mugiarsih; Budi Herminto (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2013)
Background. Pain is an unpleasant sensory and emotional experienceassociated with actual or potensial tissue damage or describe in termis of suchdamage. One of many factor caused pain was surgery. Relaxation technique isone nonpharmacological intervention to reduce pain in patients with postoperative.Purpose. This study was to determine the effect of relaxation technique toreduce pain on patients post operative at Dr.Oen Solo Baru hospital.Method. This study used pre and post experiment design. The samplingtechnique used consecutive sampling wth total number subject of sampling were25 patients. The pain scale was measured before and after intervention. Datawas analyzed by paired t-test statistical test with significance level Î± 0.05 and thedegree of permanence (dk) : 24Conclusion The result shoed t : 2.064 means that t count > t table(7.855>2.064). it can be concluded that relaxation technique can reduce pain onpatients post operative at Dr.Oen Solo Baru Hospital.Keywords : Relaxation Techniques, Pain Scale, Post Operative